1995
DOI: 10.1148/radiology.197.3.7480763
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament tear: prospective evaluation of diagnostic accuracy of middle- and high-field-strength MR imaging at 1.5 and 0.5 T.

Abstract: Higher field strength does not confer higher accuracy in the diagnosis of ACL tears at MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…The mean qualitative score for lesion conspicuity for both readers and the quantitative SDNRs were significantly lower for the .2-T system for both T1-and T2-weighted images. This fact has already been demonstrated by other investigators for knee examinations (15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The mean qualitative score for lesion conspicuity for both readers and the quantitative SDNRs were significantly lower for the .2-T system for both T1-and T2-weighted images. This fact has already been demonstrated by other investigators for knee examinations (15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 74%
“…Several reports have evaluated the accuracy of low and mid field scanners in abnormalities of the knee, with little attention to the foot and ankle (15)(16)(17)(18)(19), although the value of MRI has been demonstrated in bone injuries, tendon tears, avascular necrosis and osteochondritis dissecans, chronic instability, diabetic osteoarthropathy, and osteomyelitis. The mean qualitative score for lesion conspicuity for both readers and the quantitative SDNRs were significantly lower for the .2-T system for both T1-and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by using a low field dedicated extremity MRI system with a short data acquisition protocol [8,9]. Although the low field strength and shortening of the MRI protocol reduce image quality compared with a standard MRI examination, it has been demonstrated that lower magnetic field strength does not substantially reduce the diagnostic performance for most traumatic knee abnormalities [1,[10][11][12]. The information obtained from MRI could be sufficient to reduce the time to completion of the diagnostic workup and to influence the treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Although a higher-field strength is supposed to confer higher accuracy in the diagnosis of ACL tears, Vellet et al could not prove a higher accurancy comparing 0.5 and 1.5 T MR imaging [45]. Recently high-field strength 3 T imaging has become available for routine clinical use.…”
Section: Discussionmentioning
confidence: 99%